Lung cancer screening in the population aged 55-75 years using low-dose computed tomography (LDCT) scan in Chiang Kham Hospital Phayao, Thailand: A Cross-Sectional Observational Pilot Study - Thanawutthikul, Kritsada; Khampa, Kornchawan; Chumnumphon, Kaweewat; Chaikanta, Warachan; Piananurak, Namfon; Malairungsakul, Naruenan (Health Science, Science and Technology Reviews, 2025)
This research was to survey the prevalence of lung cancer by screening with low-dose computerized tomography (LDCT) in high-risk populations and to study the factors associated with lung cancer. A cross-sectional observational pilot study was conducted in a sample of 100 Thai people who aged between 55 and 75 years-old in Chiang Kham District, Phayao Province, during August 3rd, 2024 - December 31th, 2024. The instruments included a patient data record form and important risk factors, a digital chest X-ray (CXR AI) and a low-dose computed tomography (LDCT) result record form. We analyzed the relationship between high-risk LDCT results and other associated factors using multiple logistic regression, with statistical significance at p-value < 0.05. In the total of 100 samples, with an average age of 64 years–old, abnormal CXR AI readings were 72%. In the abnormal readings, 18% of them were lung nodules. In those lung nodule results, there was 14% of High Risk LDCT in Lung-RADS category 3 or higher. On the LDCT screening of the samples, the solid nodule was 75% of abnormal results. Most of the solid nodules were smaller than 8mm which were 36%. A Multivariable logistic regression analysis showed the statistically significant related factor with high risk LDCT, specifically the volatile substances (OR 9.59, 95%CI 1.33-70.16, p = 0.02), alcoholic drinker (OR 7.73, 95% CI 0.86-69.63, p= 0.06) and old age (OR 1.16, 95% CI 0.99-1.35, p= 0.005). The use of CXR AI for initial screening increased the chance of detecting abnormal LDCT examination with Sensitivity Specificity 100% was 32.56%, NPV was 100%, and PPV was 19.44% respectively.